Diet Modulates the High Sensitivity to Systemic Infection in Newborn Preterm Pigs - Bæk, Ole; Brunse, Anders; Nguyen, Duc Ninh; Moodley, Arshnee; Thymann, Thomas; Sangild, Per Torp (Frontiers in Immunology, 2020)
Background. Preterm infants are born with an immature immune system, limited passive immunity and are at risk of developing bacteremia and sepsis in the postnatal period. We hypothesized that enteral feeding, with or without added immunoglobulins, improves the clinical response to systemic infection by coagulase negative staphylococci. Methods. Using preterm cesarean delivered pigs as models for preterm infants, we infused live Staphylococcus epidermidis (SE, 5x109 colony forming units per kg) systemically 0-3 days after birth across five different experiments. SE infection responses were assessed following different gestational age at birth (preterm versus term), enteral milk diets (bovine colostrum, infant formula with or without added porcine plasma) and with/without systemic immunoglobulins. Pigs infected with SE were assessed 12-48 hours for clinical variables, blood bacteriology, chemistry, hematology and gut dysfunction (intestinal permeability, necrotizing enterocolitis lesions). Results. Adverse clinical responses and increased mortality were observed in preterm versus term pigs, when infected with SE just after birth. Feeding bovine colostrum just after birth improved blood SE clearance and clinical status (improved physical activity and intestinal structure, fewer bone marrow bacteria), relative to pigs fed infant formula. A few days later, clinical responses to SE bacteremia (hematology, neutrophil phagocytic capacity, T cell subsets) were less severe, and less affected by different milk diets, with or without added immunoglobulins. Conclusion. Prematurity increases the sensitivity of newborn pigs to SE bacteremia, potentially causing sepsis. Sensitivity to systemic SE infection decreases rapidly in the days after preterm birth. Both age and diet (parenteral nutrition, colostrum, milk, formula) may influence gut inflammation, bacterial translocation and systemic immune development in the days after birth in preterm newborns.